SERVICE LIFE PREDICTION FOR CONCRETE COMPOSITE WITH CARBON FIBRES FOR MARINE ENVIRONMENT - Geetha, S; Selvakumar, M (MATTER: International Journal of Science and Technology, 2018)
As construction technologies are improved and as we go for advanced technologies in construction of infrastructure facilities the importance of concrete technology is also more demanding. The field of concrete technology has many new admixtures which improves the properties of concrete. Durability and performance of structures are the main focus now. In view of this, apart from just proportioning a concrete mix, researchers are now interested in testing the performance of the material in varied environmental conditions. Service life prediction is the evaluation of the performance of the structure over a period of time. The prediction involves knowledge of materials science, laboratory testing and data from structures that are in service. It is a complex area where interpretation of correct data has been used and it involves systematic approaches. Researchers have used numerous methodologies and mathematical formulae that are used for the service life prediction. Accelerated laboratory tests forms the basis for these kinds of predictions. This paper deals with proportioning of concrete composite that can be used in aggressive marine environment, subject to severe exposure and the service life prediction of the material in such environment. Admixtures play a major role in making concrete durable. This paper discusses the properties of concrete composite that has been customized with silica fume, fly ash and copper slag for improving the strength of concrete. Carbon fibres have been added to resist the impact of sea waves and also to improve the flexural toughness of concrete. As there are various factors that have been considered in proportioning this particular concrete mix, experimental trials have been designed with reference to central composite design of Response Surface methodology using Design Expert software. The trials were cast using these design mixes and tests were conducted for strength properties and durability parameters. The experimental results have been analyzed for ANOVA to test the accuracy of results. Multiple optimizations have been done to get the best mix with maximum strength and minimum durability issues.